COMPUTER TECHNOLOGIES OF VERIFICATION OF KNOWLEDGE BASED ON THE METHOD OF SEQUENTIAL ANALYSIS - Kuzma, K. T. (Radio Electronics, Computer Science, Control, 2017)
Context. The actual task of increasing the effectiveness of decision support in the statistical control of knowledge has been solved. Objective is а development of a computational procedure for solving the problem of classification the educational process participants into four groups, according to their trainability level that allows to control knowledge differently, minimizing the amount of tasks required to accomplished. Method. The computer technology for classification the educational process participants into four groups, according to their trainability level: “initial”, “medium”, “sufficiently”, “high”, has been proposed, based on the use of sequential hypothesis testing procedure and allows to perform the controlling of the knowledge while accomplishing tasks, thus minimizing the time for testing and provides the automation of the process of verification the statistical hypotheses in a testing and learning systems with the purpose of differential assessment of knowledge the educational process participants. To solve the problem of definition the assessment standard the method based on creation the function of operational characteristics of sequential criteria is used. The function allows to establish a link between the expected probability of the hypothesis and random probability of the fact of presence in the sample with 1.2 ...n questions appropriate number of incorrect answers. Results. The software implementing proposed computational procedure have been developed and used in computational experiments of knowledge testing. Conclusions. The experiments confirmed the efficiency of the proposed procedure and software. The experiments also allow to recommend them for use in practice to solve the problems of automated assessment of knowledge.